2010
DOI: 10.1007/s11244-010-9592-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Si/Al Ratio on the Distribution of OH Groups in Zeolites with MWW Topology

Abstract: A series of MWW-type zeolites of increasing Si/Al ratio were investigated with respect to their acidic properties. Concentration of the Brønsted acid centers located at the external crystal surface was invariant for the entire series. Ethanol conversion to ethyl-tert-butyl ether, proceeding only at the external surface, was also constant. The OH groups in MWW zeolites were found to be homogeneous with proton affinity value equal to 1142.7 kJ/mol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 45 publications
3
32
0
1
Order By: Relevance
“…This indicated that most of the Al atoms were incorporated within the MWW framework in the product obtained by the seed-assisted synthesis with the OSDA-free gel. After deconvolution of overlapped signals fitted with Lorentzianf unctions (Figure 3d,e, dotted lines), the possible ratio of (T 2 :T 1 + T 3 + T 4 + T 5 + T 8 :T 6 + T 7 )f or seeds and the product are (32:45:23) and (24:53:22), respectively.T he higherc oncentration of Al atoms in T 1 + T 3 + T 4 + T 5 + T 8 sites compared to T 6 + T 7 sites for the seeds is similart ot he result reported by Gil et al [45] Thep resente valuation also indicates that the product contains more Al atoms occupied in the T 1 + T 3 + T 4 + T 5 + T 8 sites than the seeds, whichw ill be discussed in later section. It is widely acknowledgedt hat the MWW framework structure contains eight possible crystallographically nonequivalentt etrahedral Tsites for location of Al atoms.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…This indicated that most of the Al atoms were incorporated within the MWW framework in the product obtained by the seed-assisted synthesis with the OSDA-free gel. After deconvolution of overlapped signals fitted with Lorentzianf unctions (Figure 3d,e, dotted lines), the possible ratio of (T 2 :T 1 + T 3 + T 4 + T 5 + T 8 :T 6 + T 7 )f or seeds and the product are (32:45:23) and (24:53:22), respectively.T he higherc oncentration of Al atoms in T 1 + T 3 + T 4 + T 5 + T 8 sites compared to T 6 + T 7 sites for the seeds is similart ot he result reported by Gil et al [45] Thep resente valuation also indicates that the product contains more Al atoms occupied in the T 1 + T 3 + T 4 + T 5 + T 8 sites than the seeds, whichw ill be discussed in later section. It is widely acknowledgedt hat the MWW framework structure contains eight possible crystallographically nonequivalentt etrahedral Tsites for location of Al atoms.…”
Section: Resultssupporting
confidence: 85%
“…Here, T 1 ,T 2 ,T 3 ,T 4 ,T 6 ,a nd T 7 sites are located in the supercage, whereas T 5 and T 8 sites are located in the sinusoidal channel. After deconvolution of overlapped signals fitted with Lorentzianf unctions (Figure 3d,e, dotted lines), the possible ratio of (T 2 :T 1 + T 3 + T 4 + T 5 + T 8 :T 6 + T 7 )f or seeds and the product are (32:45:23) and (24:53:22), respectively.T he higherc oncentration of Al atoms in T 1 + T 3 + T 4 + T 5 + T 8 sites compared to T 6 + T 7 sites for the seeds is similart ot he result reported by Gil et al [45] Thep resente valuation also indicates that the product contains more Al atoms occupied in the T 1 + T 3 + T 4 + T 5 + T 8 sites than the seeds, whichw ill be discussed in later section. Althought he detailed mechanism for Al siting is still unclear, the above resultsb y 27 Al DD-MASN MR spectroscopy suggest that the local distribution of T-sites such as Al atoms within the MWW framework could be different depending on the syntheticm ethodology adopted (OSDA-directed or seed-assisted with OSDA-free gel).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Hence, we see no need to make any significant change in what was said in our article. Moreover, as a matter of fact, all protonic zeolites show some degree of heterogeneity in their structural Si(OH)Al Brønsted acid hydroxyl groups, which arises from the fact that the corresponding tetrahedrally coordinated aluminium atoms are not symmetrically identical [8][9][10]; and yet when applying the usual OH method to rank zeolite Brønsted acidity, OH is very commonly (although not always) measured [10][11][12][13][14][15][16][17] as the peak to peak distance between the experimentally determined O H stretching band and the corresponding red shifted band after interaction with the (weak base) IR probe molecule; and, in particular, that was the case for all of the zeolites listed in Table 1.…”
mentioning
confidence: 99%